Doctrinal Reconstruction of Pacta sunt servanda: Contractual Binding Force, Legal Certainty, and Corrective Justice - Aris Yulia; Fatma Ayu Jati Putri (Politeknik Siber Cerdika Internasional, 2026)
Background: … Objective: This study examines the reconstruction of the philosophical foundation of the binding force of contracts from the perspectives of legal certainty and justice. It addresses two central issues: first, how the paradigm of freedom of contract influences the existence of the principle of pacta sunt servanda; and second, what philosophical foundations underpin the validity of this principle within legal systems. Methods: This research employs a normative juridical method, characterized as qualitative and comparative. It is based on library research, utilizing primary and secondary legal materials analyzed qualitatively through normative and comparative legal approaches. Results: The findings reveal that, first, within the paradigm of freedom of contract or autonomy of will, there exists an operational foundation that legitimizes the binding force and enforcement of contracts as a manifestation of respect for the parties’ agreement. Second, in classical contract law theory, the doctrine of the sanctity of contract serves as a fundamental principle arising from freedom of contract and underpins the application of pacta sunt servanda. Meanwhile, in Islamic law, the philosophical foundation of the binding force of contracts is directly rooted in the normative values derived from the Qur’an, emphasizing the obligation to fulfill agreements as both a moral and legal duty. Accordingly, the reconstruction of the philosophical foundation of the binding force of contracts should not solely rely on principles of freedom and legal certainty but must also incorporate the dimension of justice as a corrective to the absolutism of freedom of contract in modern legal practice. Conclusion: …